2022
DOI: 10.1007/s10238-022-00915-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of poor prognosis in ANCA-associated vasculitis (AAV): a single-center prospective study of inpatients in China

Abstract: To identify potential predictors by assessing adverse outcomes in ANCA-associated vasculitis (AAV) patients. Eighty-nine untreated AAV patients were followed up to January 31, 2022, death, or loss of follow-up. Clinical characteristics, laboratory tests, treatment, and progress were collected, and disease activity was evaluated via Birmingham Vasculitis Activity Score (BVAS). We determined risk factors of high-risk events, defined as developing tumors, renal replacement therapy (RRT), and death. Patients and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…[ 22 ] Several retrospective studies have substantiated age as a significant prognostic determinant for mortality in individuals diagnosed with AAV. [ 23 , 24 ] A study conducted in Korean revealed that elderly patients diagnosed with AAV exhibited a notably higher all-cause mortality rate when contrasted with their non-elderly counterparts. [ 25 ] Due to the advanced age of the patient cohort, a higher prevalence of comorbidities and an overall compromised health status can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…[ 22 ] Several retrospective studies have substantiated age as a significant prognostic determinant for mortality in individuals diagnosed with AAV. [ 23 , 24 ] A study conducted in Korean revealed that elderly patients diagnosed with AAV exhibited a notably higher all-cause mortality rate when contrasted with their non-elderly counterparts. [ 25 ] Due to the advanced age of the patient cohort, a higher prevalence of comorbidities and an overall compromised health status can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is an autoimmune disease that causes severe inflammation in small vessels [1]. AAV can also result in multi-organ dysfunction, including glomerulonephritis and interstitial pneumonitis, often resulting in a poor prognosis [2,3]. Therefore, early initiation of intensive immunosuppressive therapy is recommended to improve the prognosis.…”
Section: Introductionmentioning
confidence: 99%